PENGARUH KONSUMSI PISANG AMBON DAN JUS MENTIMUN TERHADAP PENURUNAN TEKANAN DARAH PADA IBU MENOPAUSE YANG MENGALAMI HIPERTENSI DI PUSKESMAS CIGEULIS TAHUN 2025 - Repi Apriandini; Meinasari Kurnia Dewi; Milka Anggreni K; Etin Darliah; Rizka Febriyanti; Rosi Rosmiawati; Rosita Malinda (Bajang Institute, 2025)
Menopausal women were prone to hypertension due to hormonal changes that Menopausal women were prone to hypertension due to hormonal changes that decreased blood vessel elasticity. Non-pharmacological management, such as consuming foods high in potassium and antioxidants, served as an effective alternative to reduce blood pressure. Cucumbers and Ambon bananas were natural ingredients containing nutrients that supported this effort. This study aimed to determine the effectiveness of cucumber juice and Ambon bananas in lowering blood pressure among menopausal women. The method used was a qualitative study with a descriptive case study approach involving 10 menopausal women divided into two intervention groups. Group A was given 200 ml of cucumber juice every morning for seven days, while Group B was given 200–300 grams of Ambon bananas every morning for seven days. The results showed that Ambon banana consumption reduced the average blood pressure from 155/102.6 mmHg to 142.2/94.8 mmHg, while cucumber juice reduced blood pressure from 155.2/103 mmHg to 138.4/91 mmHg. The reduction in blood pressure in the cucumber juice group was greater than that in the Ambon banana group, both in systolic (16.8 vs 12.8 mmHg) and diastolic (12 vs 7.8 mmHg) values. Cucumber juice and Ambon bananas were both effective in lowering blood pressure among menopausal women, with cucumber juice showing more significant results. It was recommended that menopausal women regularly consume cucumber juice as a natural alternative to help control blood pressure, accompanied by a balanced diet and a healthy lifestyle